Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio as Novel Markers for Diagnosis of Sudden Sensorineural Hearing Loss: A Systematic Review and Meta-analysis - Bahrami, Mohammad Amin; Ansari, Abdollah; Ara, Kefayat Chaman; Bahrami, Elham; Bahrami, Sima; Bahrami, Mohammad Nabi; Barati, Omid; Moosazadeh, Mahmood; Kum, Rauf O?guzhan (BALI MEDICAL JOURNAL, 2016)
Background: Sudden sensorineural hearing loss (SSNHL) is a common otologic disease characterized by a loss of hearing greater than 30 dB in three consecutive frequencies which occurs in less than 72 hours. Objective: To investigate the role of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) on sudden sensorineural hearing loss (SSNHL). Search strategy: A PubMed, Science Direct, Scopus, OVID, EMBASE and Google Scholar search (date last searched April 2016) without any time, language and location restriction was done. Inclusion criteria: All case-control studies, which have been investigated the relationship of NLR and PLR with the occurrence of SSNHL were included in our meta-analysis. Results: A total of 5 case-control studies were included in the study. All 5 studies have been reported NLR of patients and control groups (611 patients and 804 controls). Our analysis showed that the mean NLR of patients is 1.12 (0.82-1.43) unit higher than that of controls with 95% CI which is statistically significant. Also, 3 studies have been reported PLR of patients and control groups (512 patients and 705 controls). Our analysis showed that the mean PLR of patients is 0.57 (0.08-1.05) unit higher than that of controls with 95% CI which is statistically significant too. Conclusions: This metaanalysis confirmed the relationship of NLR and PLR with SSNHL. Therefore, these parameters can be considered as new markers in diagnosis of SSNHL.